Financial Toxicity in Head and Neck Cancer Patients Treated With Proton Therapy - Grace L. Smith, MD, PhD, MPH; Ya-Chen Tina Shih, PhD; Steven J. Frank, MD (International Journal of Particle Therapy, 2021)
Cancer-related financial toxicity impacts head and neck cancer patients and survivors. With increasing use of proton therapy as a curative treatment for head and neck cancer, the multifaceted financial and economic implications of proton therapy—dimensions of “financial toxicity”—need to be addressed. Herein, we identify knowledge gaps and potential solutions related to the problem of financial toxicity. To date, while cost-effectiveness analysis has been used to assess the value of proton therapy for head and neck cancer, it may not fully incorporate empiric comparisons of patients’ and survivors’ lost productivity and disability after treatment. A cost-of-illness framework for evaluation could address this gap, thereby more comprehensively identifying the value of proton therapy and distinctly incorporating a measurable aspect of financial toxicity in evaluation. Overall, financial toxicity burdens remain understudied in head and neck cancer patients from a patient-centered perspective. Systematic, validated, and accurate measurement of financial toxicity in patients receiving proton therapy is needed, especially relative to conventional photon-based strategies. This will enrich the evidence base for optimal selection and rationale for payer coverage of available treatment options for head and neck cancer patients. In the setting of cancer care delivery, a combination of conducting proactive screening for financial toxicity in patients selected for proton therapy, initiating early financial navigation in vulnerable patients, engaging stakeholders, improving oncology provider team cost communication, expanding policies to promote price transparency, and expanding insurance coverage for proton therapy are critical practices to mitigate financial toxicity in head and neck cancer patients.